Determining the Type Of Skybridge From The Bojonggede Station to The Bojonggede Terminal Considering The Traffic Impact - Sofian Ari Saputra; Rinda Karlinasari; Rachmat Mudiyono (Kadiri University, 2022)
Bojonggede Station, located in Bogor Regency, is one of the KRL stations used to support the mobility of the surrounding community. This makes Bojonggede station a place with quite complex transportation problems. From the various problems that occur, this research aims to find the right sky bridge to connect the bojonggede station with the bojonggedeTerminall and reduce the impact of traffic in the surrounding location after the sky bridge. The data analysis method used is the 4 step model method consisting of trip generation/attraction, trip distribution, mode selection (Moda Split), trip assist, Indonesian road capacity manual, and descriptive analysis of survey data on visitors Bojonggede station. From the results of the analysis based on the 4 step model and manual of Indonesian road capacity, it is found that the performance of the Bojonggede 2 highway, which is in front of the location, has increased from LOS F during the construction period to LOS C during the sky bridge operations bridged. The benefit of this research is that it can be seen that traffic problems that occur at the study site can be overcome by the existence of an efficient sky bridge design sky bridges Bojonggede station with Bojonggede Terminal, to be further recommended to the Bogor district transportation office, and the Jabodetabek transportation management center ( BPTJ).